Empathetic AI Feedback in English Language Learning: Enhancing Student Engagement and Reducing Anxiety in MAN Labuhanbatu Utara - Nursaima Harahap (Yayasan Insan Cipta Medan, 2025)
This study explores the impact of empathetic AI feedback on English language learners at MAN Labuhanbatu Utara, specifically focusing on enhancing student engagement and reducing anxiety. In the context of language learning, anxiety is a significant barrier that can affect students' motivation and performance. The study investigates how AI-driven feedback, which incorporates emotional intelligence, can foster a more supportive and engaging learning environment. A mixed-method approach was used, combining surveys, classroom observations, and interviews. The results indicated a marked reduction in student anxiety, particularly in areas such as fear of making mistakes and peer judgment. Furthermore, students who received empathetic AI feedback exhibited higher levels of engagement, participating more actively in class activities and demonstrating increased motivation. These findings suggest that integrating emotionally supportive AI feedback into language learning can create a more positive and effective educational experience, potentially improving both emotional well-being and academic performance.